Analisis Breakdown Selang Plougshare M109 di Pabrik Phonska I PT Petrokimia Gresik Menggunakan Metode RCA - Lilmumazzaini, Farista; Lilmumazzaini, Sumiati (Jurnal Serambi Engineering, 2025)
The purpose of this study is to analyze the root causes of the plowshares hose failures in the rotary pelletizer (M109) at Phonska I Plant, PT Petrokimia Gresik, which frequently experience tearing, detachment, and leakage. The Root Cause Analysis (RCA) method using Fishbone Diagram and 5 Whys was applied to identify the root causes. Data was collected from the shutdown and work order history of the M109 equipment during January-November 2024. The analysis revealed that the root causes were lack of installation and inspection SOPs, inappropriate hose materials for operating conditions, and high machine vibration. Recommended improvements include developing SOPs for installation and inspection, using high-quality hose, and installing pressure and vibration monitoring equipment. Implementation of these recommendations is expected to improve machine reliability and reduce the frequency of failures.